Bi-allelic mutations in DNAH7 cause asthenozoospermia by impairing the integrality of axoneme structure. (3rd September 2021) - Wei, Xiaoli; Sha, Yanwei; Wei, Zijie; Zhu, Xingshen; He, Fengming; Zhang, Xiaoya; Liu, Wensheng; Wang, Yifeng; Lu, Zhongxian
Abstract: Asthenozoospermia is the most common cause of male infertility. Dynein protein arms play a crucial role in the motility of both the cilia and flagella, and defects in these proteins generally impair the axoneme structure and cause primary ciliary dyskinesia. But relatively little is known about the influence of dynein protein arm defects on sperm flagella function. Here, we recruited 85 infertile patients with idiopathic asthenozoospermia and identified bi-allelic mutations in DNAH7 (NM_018897.3) from three patients using whole-exome sequencing. These variants are rare, highly pathogenic, and very conserved. The spermatozoa from the patients with DNAH7 bi-allelic mutations showed specific losses in the inner dynein arms. The expression of DNAH7 in the spermatozoa from the DNAH7 -defective patients was significantly decreased, but these patients were able to have their children via intra-cytoplasmic sperm injection treatment. Our study is the first to demonstrate that bi-allelic mutations in DNAH7 may impair the integrality of axoneme structure, affect sperm motility, and cause asthenozoospermia in humans. These findings may extend the spectrum of etiological genes and provide new clues for the diagnosis and treatment of patients with asthenozoospermia.